2013
DOI: 10.1038/ki.2012.447
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropic hormone ameliorates acute kidney injury by steroidogenic-dependent and -independent mechanisms

Abstract: Adrenocorticotropic hormone (ACTH) has a renoprotective effect in chronic kidney disease; however, its effect on acute kidney injury (AKI) remains unknown. In a rat model of tumor necrosis factor (TNF)–induced AKI, we found that ACTH gel prevented kidney injury, corrected acute renal dysfunction, and improved survival. Morphologically, ACTH gel ameliorated TNF-induced acute tubular necrosis, associated with a reduction in tubular apoptosis. While the steroidogenic response to ACTH gel plateaued, the kidney-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 45 publications
1
41
1
1
Order By: Relevance
“…29,30,46 Finally, Acthar could prevent progression of proteinuria in the NZB/W F1 model via direct effects on podocytes, as prior evidence demonstrates MCR expression on podocytes, as well as protective effects of this drug on proteinuria in both animal and human nephrotic disease. 11,16,18 Of note, in these experiments, Acthar treatment was not associated with any identified adverse events. In contrast, prednisolone-treated NZB/W F1 mice failed to gain weight throughout the treatment period, and were more likely to require early termination from the study.…”
Section: Discussionmentioning
confidence: 86%
“…29,30,46 Finally, Acthar could prevent progression of proteinuria in the NZB/W F1 model via direct effects on podocytes, as prior evidence demonstrates MCR expression on podocytes, as well as protective effects of this drug on proteinuria in both animal and human nephrotic disease. 11,16,18 Of note, in these experiments, Acthar treatment was not associated with any identified adverse events. In contrast, prednisolone-treated NZB/W F1 mice failed to gain weight throughout the treatment period, and were more likely to require early termination from the study.…”
Section: Discussionmentioning
confidence: 86%
“…In a rat model of tumor necrosis factor (TNF)-induced acute kidney injury, Si et al (2013) found that ACTH gel prevented kidney injury, corrected acute renal dysfunction, and improved survival. Morphologically, ACTH gel ameliorated TNF-induced acute tubular necrosis, associated with a reduction in tubular apoptosis.…”
Section: Acth Also Has a Renoprotective Effect In Chronic Kidney Diseasementioning
confidence: 99%
“…Urine creatinine was measured by a creatinine assay kit (BioAssay Systems, Hayward, CA). Blood pressure was measured using the tail cuff method as described previously (41). Mice were sacrificed on day 3, 7, 14, or 28.…”
Section: Animal Experimental Designmentioning
confidence: 99%
“…Tetrazolium was released by dimethyl sulfoxide, and the optical density was determined with a spectrophotometer at 570 nm reader as before (41).…”
Section: Tetrazolium Assay For Cellular Viabilitymentioning
confidence: 99%